FATIGUE ANALYSIS OF CATENARY MOORING SYSTEM DUE TO HARSH ENVIRONMENT IN FOLLOWING SEAS - Assidiq, Fuad Mahfud; Paroka, Daeng; Alie, Muhammad Zubair Muis; Klara, Syerly (Jurnal Indonesia Emas PPI Dunia, 2018)
In the operation, Floating Production Unit (FPU) will get dynamic loads on the structure periodically such as the mooring line responses. The aim of the present study to discuss fatigue life on catenary mooring system refers to the comparison of using or without using the Single Line Freestanding Riser (SLFR), the operational design and installation conditions at FPU Gendalo-Gehem and located in the Makassar Strait using the six-strand wire rope with 0,115 meters outer diameter and 1.200 meters length will be fatigue life analysed. The FPU motion observation shows the highest Response Amplitude Operator (RAO) surge, sway, heave, roll, pitch, and yaw motion due to harsh environments are 0,615 m/m, 1,01x10-6 m/m, 1,048 m/m, 1,14x10-5 0/m, 2,23 0/m, and 9,08x10-8 0/m. It means that the amplitude response will always be smaller than the wave amplitude coming up. Taking into RAO motion calculation, the fatigue life on catenary mooring systems for following seas are 445 years in mooring line 1 and mooring line 8 with using SLFR while without using SLFR for 5.461 years in mooring line 1. The structure is still in safe condition because of the design safety factor about 300 years.